1978
DOI: 10.1111/j.1745-6606.1978.tb00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Informational Inputs as Influences on Efficient Consumer Decision‐Making

Abstract: The effects of consumer information and consumer sophistication on the ability of consumers to make purchases offering the greatest benefits were examined. It was found that consumer information enhances the likelihood that consumers will make efficient choices of products. Consumer sophistication was also found to be an intervening variable in consumers' use of information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 5 publications
3
41
0
1
Order By: Relevance
“…• Lack of information leads to low customer awareness of both ethical issues and available products. This is in line with Sproles et al (1978) who argued that efficient decisions making requires consumers to be fully informed, however, Boulstridge and Carrigan (2000) found that most consumers lack information to distinguish whether a company has or has not behaved ethically. This appears an even greater problem in luxury purchases due to their irregularity of purchase and therefore the information salience.…”
Section: Discussionsupporting
confidence: 50%
“…• Lack of information leads to low customer awareness of both ethical issues and available products. This is in line with Sproles et al (1978) who argued that efficient decisions making requires consumers to be fully informed, however, Boulstridge and Carrigan (2000) found that most consumers lack information to distinguish whether a company has or has not behaved ethically. This appears an even greater problem in luxury purchases due to their irregularity of purchase and therefore the information salience.…”
Section: Discussionsupporting
confidence: 50%
“…Adequate decision-making requires a full understanding of the related conditions and circumstances (Sproles & Badenhop, 1978). Media is a crucial information source for consumers and although there are individuals that have some background knowledge about ethical products, confusion-as well as cynicism-is still predominant when thinking about ethical alternatives (Carrigan & Attalla, 2001).…”
Section: Environmental Knowledgementioning
confidence: 99%
“…Consumers possess different information-processing abilities that influence their product choices. Sproles, Geistfeld, and Badenhop (1978) examined how much information consumers need in order to make efficient purchase decisions. Results showed that the more information provided, the more efficient the purchasing decisions.…”
Section: Motivational Variablesmentioning
confidence: 99%